Thinking about the past, present, and future: Time perspective and self‐esteem in adolescents, young adults, middle‐aged adults, and older adults. (15th August 2021) - Mello, Zena R.; Barber, Sarah J.; Vasilenko, Sara A.; Chandler, Julie; Howell, Ryan
Abstract : We examined time perspective and self‐esteem in adolescents, young adults, middle‐aged adults, and older adults. Time perspective was measured with scales that assess relative orientations and relationships among the past, present, and future. Age effects were examined with standard analytic strategies to determine categorical differences between age groups and with new statistical techniques designed to show continuous age patterns. Findings indicated that (1) thinking about the future was greatest for adolescents and young adults and lowest for middle‐aged and older adults, and thinking about the present increased across ages; (2) fewer adolescents and middle‐aged participants perceived that the time periods were interrelated compared to younger and older adults; and (3) across ages, a greater emphasis towards the past compared to other time periods was associated with lower self‐esteem, whereas emphasizing the present and the future jointly was associated with higher self‐esteem.